Principales aspectos para la exportación de Tilapia entera congelada y Tilapia entera fresca a mercados internacionales desde el departamento de Huila (2023)
The purpose of this research is to determine the main aspects that must be taken into account to export frozen whole Tilapia and fresh whole Tilapia in order to increase production and profitability of companies in Huila - 2023. The methods used included direct observation, primary and secondary information regarding the production process of the selected tariff items: frozen whole Tilapia and fresh whole Tilapia, which have high potential in Huila and can be extensively exported. Additionally, a target market selection matrix, logistical chain for exportation, study of supply and demand, analysis of international prices, as well as a quotation from the AS national cargo transportation company from Neiva - Huila to the port of Cartagena - Bolívar were conducted. The research proposal is based on Time Study and digital statistical tools such as Trade Map, Procolombia, and Legiscomex, which are related to the reality and objectives of this thesis work.